Pengaruh Program Keagamaan Terhadap Perilaku Belajar Siswa di MI Nurul Athhar Kebonsari - Nafia, Iin Mila; Habibah, Nur Faiz; Almuftiyah, Almuftiyah (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Students’ ability to read and understand the Qur’an and carry out the obligation of prayer is an important aspect in spiritual development at the elementary level. Students with strong spirituality tend to have better learning behavior. Madrasah Ibtidaiyah plays a role in spiritual development through various religious programs to strengthen students’ religious values. This study aims to analyze the effect of the tahfidz program, congregational prayer program, and religious programs on students’ learning behavior at MI Nurul Athhar Kebonsari. This study used a field study method with a population of 198 students and a sample of 65 students. Data collection techniques included documentation institutions, questionnaires, and interviews. Data analysis was carried out using IBM SPSS version 27. The results of the study showed that: (1) The tahfidz program had a significant effect on students’ learning behavior with a sig. value of 0.00 <0.05 and tcount (9.989) > ttable (1.669). (2) The congregational prayer program also had a significant effect with a sig. value. 0.00 < 0.05 and tcount (11.518) > ttable (1.669). (3) The religious program as a whole has a significant effect on student learning behavior with a value of Fcount (89.983) > Ftable (3.145) and sig. 0.00 < 0.05. Based on these results, it can be concluded that the tahfidz program, congregational prayer program, and religious programs have a positive and significant effect on student learning behavior. Therefore, strengthening religious programs in madrasas can be an effective strategy in improving the quality of student learning.